Neuro-Oncology Clinicians' Attitudes and Perspectives on Medical Assistance in Dying. (29th November 2021) - Climans, Seth A.; Mason, Warren P.; Variath, Caroline; Edelstein, Kim; Bell, Jennifer A. H.
ABSTRACT: Background: Medical assistance in dying (MAiD), also known as physician-assisted death, is currently legal in several locations across the globe. Brain cancer or its treatments can lead to cognitive impairment, which can impact decision-making capacity for MAiD. Objective: We sought to explore neuro-oncology clinicians' attitudes and perspectives on MAiD, including interpretation of decision-making capacity for patient MAiD eligibility. Methods: An online survey was distributed to members of national and international neuro-oncology societies. We asked questions about decision-making capacity and MAiD, in part using hypothetical patient scenarios. Multiple choice and free-text responses were captured. Results: There were 125 survey respondents. Impaired cognition was identified as the most important factor that would signal a decline in patient capacity. At least 26% of survey respondents had moral objections to MAiD. Respondents thought that different hypothetical patients had capacity to make a decision about MAiD (range 18%–58%). In other hypothetical scenarios, fewer clinicians were willing to support a MAiD decision for a patient with an oligodendroglioma (26%) vs. glioblastoma (41%–70%, depending on the scenario). Time since diagnosis, performance status, and patient age seemed to affect support for MAiD decisions (Fisher's exact P -values 0.007, < 0.001, and 0.049, respectively). Conclusion: While there are differing opinions on the moral permissibility of MAiD in general and for neuro-oncology patients, most clinicians agree that capacity must be assessed carefully before a decision is made. End-of-life discussions should happen early, before the capacity is lost. Our results can inform assessments of patient capacity in jurisdictions where MAiD is legal.